The Manufacturing Of Polyamide- And Polypropylene-Organoclay Nanocomposite Filaments And Their Suitability For Textile Applications - Önder, Emel; Ersoy, M. Sabri; SARIER, NİHAL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2012)
In this study, we prepared polymer-clay monofilaments using a melt spinning technique in which organoclays were incorporated into polyamide 6 (PA6) and polypropylene (PP) homopolymer resins. The structural and thermal characterizations of the monofilaments were performed by Fourier transform infrared spectrometry (FTIR), scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and thermogravimetric (TG) analyses. The detailed mechanical and dynamic mechanical analyses (DMA) of the nanocomposite filaments were conducted to evaluate their mechanical performances in relation to the type and ratio of organoclays incorporated into the structure. Thermal analysis, tensile rest and dynamic mechanic analysis results show that the properties of the nanocomposite fibers were considerably more desirable compared with those of ordinary PP and PA6 fibers. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: polyamide 6; polypropylene; organoclay; fiber; thermal property; DMA; nylon 6-clay hybrid; mechanical-properties; nonisothermal crystallization; polymer nanocomposites; 6/clay nanocomposites; tensile properties; part 1; clay; composites; behavior; polyamid 6; polipropilen; organokil; lif; termal özellik; naylon 6-Toprak hibrid; mekanik özellikler; izotermal olmayan kristalleşme; polimer nanokompozitler; 6 / kil nanokompozitler; gerilme özellikleri; bölüm 1; kil; kompozitler; davranış